Pengembangan Media Pembelajaran Scrapbook Berbasis Canva Pada Tema 8 Subtema 1 Untuk Siswa Kelas V Sd Negeri 16 Urat Timur T.A 2022/2023 - Rotua Situmorang; Erlinda Simanungkalit; Demmu Karo-karo; Eva Betty Simanjuntak; Lidia Simanuhuruk (Lembaga Pengembangan Kinerja Dosen, 2023)
This study focuses on analyzing the validity of developing learning media, knowing the practicality and effectiveness of developing Canva-based scrapbook learning media on the theme 8 sub-themes 1 learning 4 class V SD Negeri 16 Urat Timur T.A 2022/2023. The problem in this study is that the learning media used in the learning process are still conventional media, the lack of use of learning media that utilizes technology, students find it difficult to understand learning material, and learning is still teacher- centered so that students are less active in the learning process. This research is a development research (Research and Development) using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The subjects of this study were fifth grade students and the object of this research was Canva-based scrapbook learning media. The results of material validation by material experts obtained a percentage of 85% in the